Pengaruh Kompensasi Terhadap Produktivitas Kerja di PT BSI Kantor Cabang Bandung Selatan - Yasir M Fauzi; Jiwa Riwayanti; Yuni Maryanti (Prodi Ekonomi Syariah Universitas Majalengka, 2026)
Based on the results of observations and interviews, this study was motivated by a decrease in the number of employees at PT Bank Syariah Indonesia (BSI) South Bandung Branch Office, which was known to be caused by a lack of compensation for work results. The purpose of this study was to analyze the effect of compensation on employee work productivity. The research method used was associative quantitative with primary data obtained through observation, interviews, literature studies, and questionnaires. The sampling technique used saturated sampling with a population of 30 employees who were also used as research samples. The results showed that compensation had a significant effect on work productivity with a contribution of 32.5% (t count 3.674 > t table 2.04841). Thus, compensation has been proven to play an important role in increasing employee productivity at PT BSI South Bandung Branch Office.